The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004410000263
|View full text |Cite
|
Sign up to set email alerts
|

Responses of immunocompetent cells in the dental pulp to replantation during the regeneration process in rat molars

Abstract: Responses of immunocompetent cells to tooth replantation during the regeneration process of the dental pulp in rat molars were investigated by immunocytochemistry using antibodies to class II major histocompatibility complex (MHC) molecules (OX6 antibody), monocyte/macrophage lineage cells (ED1 antibody) and protein gene product 9.5 (PGP 9.5), as well as by histochemical reaction for periodic acid-Schiff (PAS). Tooth replantation caused an increase in both the number of OX6- and ED1-positive cells and their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…In contrast, class II MHC-positive cells were localized beneath the abscess lesion instead of arranging along the pulp-dentin border as in the case of pulp capping with TCP alone. These findings suggest that the accumulation of dendritic cells at the pulp-dentin border may be a prerequisite phenomenon for the differentiation of odontoblastlike cells; this is consistently observed in the pulpal repair process following tooth injuries irrespective of the types of injuries such as cavity preparation or tooth replantation reported in previous studies (Ohshima et al, 1995;Shimizu et al, 2000;Nakakura-Ohshima et al, 2003;Ohshima et al, 2003) or the direct pulp capping reported in this study. A crucial role for class II MHC-positive cells in the process of odontoblast differentiation is supported by our recent results showing that the secretions of the granulocyte-macrophage colony-stimulating factor (GM-CSF) and osteopontin by immunocompetent cells such as macrophages and dendritic cells play respective roles in the maturation of dendritic cells and the differentiation of odontoblasts in the regenerated pulp tissue following tooth transplantation (Saito et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, class II MHC-positive cells were localized beneath the abscess lesion instead of arranging along the pulp-dentin border as in the case of pulp capping with TCP alone. These findings suggest that the accumulation of dendritic cells at the pulp-dentin border may be a prerequisite phenomenon for the differentiation of odontoblastlike cells; this is consistently observed in the pulpal repair process following tooth injuries irrespective of the types of injuries such as cavity preparation or tooth replantation reported in previous studies (Ohshima et al, 1995;Shimizu et al, 2000;Nakakura-Ohshima et al, 2003;Ohshima et al, 2003) or the direct pulp capping reported in this study. A crucial role for class II MHC-positive cells in the process of odontoblast differentiation is supported by our recent results showing that the secretions of the granulocyte-macrophage colony-stimulating factor (GM-CSF) and osteopontin by immunocompetent cells such as macrophages and dendritic cells play respective roles in the maturation of dendritic cells and the differentiation of odontoblasts in the regenerated pulp tissue following tooth transplantation (Saito et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…In these experimental models, pulpal mesenchymal cells take the place of the degenerated odontoblasts to differentiate into odontoblast-like cells, resulting in the formation of tertiary dentin. Our recent studies using rat models have demonstrated that the temporal appearance of dendritic cells at the pulp-dentin border is a decisive phenomenon to induce the differentiation of odontoblastlike cells after tooth injuries such as cavity preparation and tooth replantation (Ohshima et al, 1995;Shimizu et al, 2000;Nakakura-Ohshima et al, 2003;Ohshima (EDTA-2Na) solution for 6 weeks at 4 , the samples were processed for cryosectioning for which the tissue blocks were equilibrated in a 30% sucrose solution for cryoprotection. The specimens were cut sagittally at a thickness of 25-50 m with a freezing microtome (FX-801; Yamato Kohki, Tokyo), collected into cold phosphate-buffered saline (PBS), and treated as freefloating sections.…”
Section: Procedures Of Cavity Preparation and Pulp Cappingmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures interrupt the nerve and vascular supply to the dental pulp and induce subsequent degeneration of the pulpal cells. In successful cases, the pulpal healing, including reinnervation and revascularization, has been shown to occur in humans (Andreasen et al 1995) and experimental animal studies (Byers et al 1992;Hasegawa et al 2007;Kvinnsland et al 1991;Nakakura-Ohshima et al 2003;Ohshima et al 2001;Rungvechvuttivittaya et al 1998;Shimizu et al 2000;Tsukamoto-Tanaka et al 2006;Unno et al 2009). Tooth replantation/transplantation induces at least two types of healing patterns in the replanted teeth: dentin and bone tissue formation in the repaired dental pulp (Byers et al 1992;Hasegawa et al 2007;Kvinnsland et al 1991;Ohshima et al 2001;Rungvechvuttivittaya et al 1998;Shimizu et al 2000;Tsukamoto-Tanaka et al 2006;Unno et al 2009).…”
mentioning
confidence: 99%
“…In successful cases, the pulpal healing, including reinnervation and revascularization, has been shown to occur in humans (Andreasen et al 1995) and experimental animal studies (Byers et al 1992;Hasegawa et al 2007;Kvinnsland et al 1991;Nakakura-Ohshima et al 2003;Ohshima et al 2001;Rungvechvuttivittaya et al 1998;Shimizu et al 2000;Tsukamoto-Tanaka et al 2006;Unno et al 2009). Tooth replantation/transplantation induces at least two types of healing patterns in the replanted teeth: dentin and bone tissue formation in the repaired dental pulp (Byers et al 1992;Hasegawa et al 2007;Kvinnsland et al 1991;Ohshima et al 2001;Rungvechvuttivittaya et al 1998;Shimizu et al 2000;Tsukamoto-Tanaka et al 2006;Unno et al 2009). Our recent studies have demonstrated that the types of cells appearing along the pulp-dentin border play crucial roles in determining the healing patterns in the replanted teeth: once osteoclast lineage cells appear at the pulp-dentin border, bone matrix deposition can be induced (Hasegawa et al 2007;Tsukamoto-Tanaka et al 2006;Unno et al 2009), whereas the temporal appearance of dendritic cells there induces dentin formation (Nakakura- Ohshima et al 2003;Shimizu et al 2000).…”
mentioning
confidence: 99%